"Whatever!" The Wonderful Possibilities of Adolescence. (April 2014) - Barrow, Giles
The purpose of this article is to challenge mainstream understanding of the function and nature of adolescence. The author explores features of adolescence common in Western culture and specifically the way in which the teenage years are perceived to provoke and antagonize older adults. He suggests that adolescents present a significant opportunity for community-supported change and development and considers ideas from neuroscience and script development (Berne, 1961). A relevant case study is offered to illustrate these issues.